Minification of fundus optical coherence tomographic images in gas-filled eye. Issue 1 (December 2016) - Yamashita, Toshifumi; Terasaki, Hiroto; Sakamoto, Taiji
Abstract Background Optical coherence tomography (OCT) is being used increasingly to evaluate and manage a variety of retinal diseases, but not much is known about the minification of the OCT images in gas-filled eyes. The purpose of this study was to investigate the effect of gas-filled eyes on the size of the OCT images. Methods This was retrospective case series of 81 consecutive eyes of 79 patients who had macular hole surgery between April 2012 and September 2014. Images of the optic disc were taken with a spectral domain-OCT instrument 2 days after surgery in gas-filled, pseudophakic eyes and from the same eyes but fluid-filled one month after the surgery. The vertical length, horizontal width, and the area of the optic disc were measured in the OCT images. Results Clear images were obtained from 50 eyes of 49 patients (mean age 66.4 ± 5.9 years). The mean vertical length and mean horizontal width of the optic disc in the gas-filled eyes were about 25 % shorter than that of fluid-filled eyes (vertical, 1213.8 ± 170.5 and 1650.6 ± 195.9 μm, P < 0.01; horizontal, 1169.4 ± 143.1 and 1526.4 ± 219.9 μm, P < 0.01). The mean area of the optic disc was 1.12 ± 0.34 mm2 in gas-filled eyes which was significantly smaller than that in fluid-filled eyes (1.88 ± 0.37 mm2 ) by 40.4 %. Conclusions The fundus images of gas-filled eyes are significantly smaller than that in the same fluid-filled eyes. The minification of the OCT images should be considered when analyzing images obtained from gas-filled eyes. Trial registration Trial registration number:UMIN000007517 . Date of registration: 3/21/2012.